Integrated Population Pharmacokinetic Analysis of Rivaroxaban Across Multiple Patient Populations. (16th April 2018) - Willmann, Stefan; Zhang, Liping; Frede, Matthias; Kubitza, Dagmar; Mueck, Wolfgang; Schmidt, Stephan; Solms, Alexander; Yan, Xiaoyu; Garmann, Dirk
Abstract : The population pharmacokinetics (PK) of rivaroxaban have been evaluated in several population‐specific models. We developed an integrated population PK model using pooled data from 4, 918 patients in 7 clinical trials across all approved indications. Effects of gender, age, and weight on apparent clearance (CL/F) and apparent volume of distribution (V/F), renal function, and comedication on CL/F, and relative bioavailability as a function of dose (F) were analyzed. Virtual subpopulations for exposure simulations were defined by age, creatinine clearance (CrCL) and body mass index (BMI). Rivaroxaban PK were adequately described by a one‐compartment disposition model with a first‐order absorption rate constant. Significant effects of CrCL, use of comedications, and study population on CL/F, age, weight, and gender on V/F, and dose on F were identified. CrCL had a modest influence on exposure, whereas age and BMI had a minor influence. The model was suitable to predict rivaroxaban exposure in patient subgroups of special interest.